The Development Of Children's Rough Motoric Through BOI CREATIVE GAME In Batubanawa Village, Mawasangka Timur District, Central Buton Regency - Eli Ernawati; Asma Kurniati; Rachman Saleh (Universitas Muhammadiyah Ponorogo, 2021)
This research aimed to know the development of children's rough motoric through Boi creative game in Batubanawa Village, Mawasangka Timur District, Central Buton regency. The method used in this research was descriptive qualitative, where descriptive qualitative research was research that studies the existing problems and working procedures that apply. The results of this research were that the development of children's rough motoric experienced the development; 8 of 9 children who played the game developed very well. This proves that Boi creation games can improve rough motoric skills of children aged 5-6 years.